The Role of Photoactivated and Non-Photoactivated Verteporfin on Tumor - Wei, Changran; Li, Xiangqi (Frontiers in Pharmacology, 2020)
Verteporfin (VP) has long been clinically used to treat age-related macular degeneration through photodynamic therapy (PDT). Recent studies have reported a significant anti-tumor effect of VP as well. YAP is a pro-tumorigenic factor that is aberrantly expressed in various cancers and is a central effector of the Hippo signaling pathway that regulates organ size and tumorigenesis. VP can inhibit YAP without photoactivation, along with suppressing autophagy, and downregulating GLK and SPK. In addition, VP can induce mitochondrial damage and increase the production of reactive oxygen species upon photoactivation, and is an effective photosensitizer in anti-tumor PDT. We have reviewed the direct and adjuvant therapeutic action of VP as a photosensitizer, and its YAP/TEAD-dependent and independent pharmacological effects in the absence of light activation against cancer cells and solid tumors. Based on the present evidence, VP may be repositioned as a promising anti-cancer chemotherapeutic and adjuvant drug.